Clinical benefit analysis of PD-1 inhibitors in patients with advanced, recurrent or metastatic cervical cancer: a meta-analysis and systematic review - Wang, Yun-zi; Wang, Ji-sheng; Du, Jiang; Tang, Xue-li; Xiao, Jing-ping (Frontiers in Immunology, 2024)
This study aims to comprehensively evaluate the efficacy and safety of PD-1 in patients with ARMCC and identify the population that may benefit the most.We conducted a search of PubMed, EMBASE, and the Cochrane Collaboration Library from their inception to September 2023. We extracted and analyzed the results related to the efficacy and safety of PD-1 in patients with ARMCC. The primary endpoints included the overall ORR and adverse events (AEs), while the secondary endpoints encompassed the 1-year OS rate, 1-year PFS rate, as well as OS and PFS. We used a random effects model to conduct a meta-analysis on single-group rates, and the Mantel-Haenszel method was utilized to compare the ORR and the incidence of AEs.Our study included a total of 21 trials involving 2,097 patients. The ORR of the combination of PD-1 inhibitors with chemotherapy was 56.36%, the combination of PD-1 inhibitors with anti-angiogenic agents was 38.72%, the combination of PD-1 inhibitors with Cytotoxic T-lymphocyte antigen 4 inhibitors was 25.60%, and PD-1 inhibitor monotherapy was 15.99%. The subgroup analysis showed that the group of patients with SCC exhibited a significantly higher ORR compared to the non-SCC group in patients who received PD-1 inhibitors combined with other anti-tumor drugs (OR =2.43, P=0.002). Additionally, the group of patients with a programmed death-ligand 1 combined positive score (PD-L1 CPS) ≥1 exhibited a significantly higher ORR compared to the PD-L1 CPS <1 group in patients who received PD-1 inhibitor monotherapy (OR=4.14, P=0.02). PD-1 inhibitor monotherapy or PD-1 inhibitors combined with chemotherapy did not significantly increase the incidence of all grades of adverse events (RR=0.99, p=0.788) or the incidence of serious adverse events (RR=0.99, p=0.788) compared to chemotherapy alone.Conclusions PD-1 inhibitors demonstrate outstanding efficacy in the treatment of patients with ARMCC. Patients with SCC may benefit more from treatments including PD-1 inhibitors in combination with other anti-tumor drugs, and PD-L1 CPS ≥1 can be considered a favorable indicator of immune therapy response. Importantly, the use of PD-1 inhibitor monotherapy or PD-1 inhibitors in combination with chemotherapy did not lead to an increased incidence of AEs compared with chemotherapy alone, indicting safety during treatment.